Synthesis of Cyanuric Chloride based Chiral Reagent for RP-HPLC Enantioseparation of (RS)-Propranolol - Al-Shehri, H.S.; Alwera, V.; Nilugal, K.C.; Joshi, K.K.; Alwera, S. (Asian Journal of Chemistry, 2022)
In this work, four cyanuric chloride based chiral reagents were prepared via nucleophile substitution of chlorine atom by L-proline derivatives and characterized by UV, FT-IR, HRMS, NMR and elemental analysis. Racemic propranolol was chosen for the chiral recognition study. The prepared chiral reagents were used in the synthesis of diastereomeric derivatives of (RS)-propranolol, under microwave heating conditions. RP-HPLC was used to separate the prepared diastereomeric derivatives. The effect of varying eluting phase concentrations and sample concentrations was optimized. The DFT calculations were performed using Gaussian 09 Rev A.02 to create the lowest energy optimised structures of diastereomeric derivatives. LOD (0.324 ng mL-1), LOQ (0.972 ng mL-1), calibration range (0.02-2.0 mg mL-1), correlation-coefficient (0.999), and recovery were the validation parameters for the present method (99.09 and 99.81 % for inter-day assay and 98.47 and 99.72 % for intra-day assay).